Five‐phase travelling wave induction heater for continuous heating of flat material. Issue 3 (2nd March 2016) - Al‐Shaikhli, Ali K.; Humod, Abdul‐Rahim T.; Hasan, Fadhil A.
Abstract : This study proposed a novel travelling wave induction heating system with five‐phase exciting current. The proposed system used special exciting current to obtain a homogeneous eddy current density, which affects the temperature pattern over the material surface. Five‐phase system has been attracted from many industrial applications due to its inherent features compared to the three‐phase system. An even number of phases is not preferred because the poles exchange with each other. A comparison investigation with other traditional methods is represented to realise the features of the proposed method. A finite‐element method simulation is represented by using ANSYS 15 ® ; the simulation results show that the proposed system gives superior performance of energy transferred, uniform heat distribution and higher power factor over that of the traditional three‐phase system. Moreover, it performs identical eddy current, power densities, temperature and efficiency to that of the six‐phase system with profits of reduction in size, weight, cost and winding copper losses.